ADVANCES IN THE EARLY LARVAL STAGES OF SIBERIAN STURGEON: MUSCLE DEVELOPMENT AND STRUCTURE UNDER DIFFERENT REARING CONDITIONS - MATELA DA SILVA AIDOS, MARIA LUCIA (Università degli Studi di Milano, 2019)
Fish larval stages are particularly sensitive to environmental conditions, as these can severely affect survival and potential growth. In fish species destined for production and commercialisation, a suitable early environment is of great importance, for what concerns growth efficiency and quality at harvest. Temperature and stocking density are among the most important factors affecting the early stages of development, regarding somatic and muscle growth of fish. Moreover, environmental enrichment is considered to improve biological functioning of captive animals, including fish, by improving their psychological and behavioral needs. Siberian sturgeon (Acipenser baerii) is a species at risk of extinction and, therefore, production of this species in aquaculture is of vital importance, not only to provide the market with caviar and meat, but also for repopulation purposes. Taking into account that little is known regarding the impact of environmental conditions in early life stages of the Siberian sturgeon, the aim of this Thesis is to provide new knowledge on the influence on muscle growth and development during the endogenous feeding phase. This was performed by addressing morphological, physiological and molecular aspects of muscle growth structure and development. This Thesis may contribute to identify and select the most suitable environmental conditions to improve Siberian sturgeon larval rearing in aquaculture production. Three trials have been performed, one in each year of my PhD, where 1) rearing temperature, 2) stocking density and 3) environmental enrichment were examined in important timepoints of Siberian sturgeon larvae development: hatching, schooling and complete yolk-sac absorption stage. In Chapter 1, is presented a general overview of Siberian sturgeon biology and development, a brief description of the muscle morphology and of the methods used to study muscle growth. Following, the types of sturgeon muscle growth are described, as well as the mechanisms involved in muscle growth regulation. ...